PENGARUH STRUKTUR ASET, PROFITABILITAS, KEPUTUSAN INVESTASI, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL - Tansyawati, Febriana; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
In the making of capital structure policy, a company requires to consider many factors in order to achieve the capital structure level which can minimize the average cost of capital and to maximize the firm value and companyâs asset. The purpose of this research is to examine the influence of assets structure, profitability, investment decision and business risk to the capital structure.The research sample consisted of 16 companies were selected by purposive sampling of properties and real estate companies listed on the Indonesia Stock Exchange during 2011-2013 The multiple regressions analysis and classic assumption test have been performed by using SPSS 20.0 version statistic test instrument. The result of the research shows that the research regression model has fulfilled the requirements there are no symptoms of heteroscedasticity, multicollinearity, and correlation and the in used file is normally distributed. The result of the research shows: (1) the structure of assets has influence to the capital structure, (2) that profitability has influence to the capital structure (3) investment decisions has influence to the capital structure, and (4) the business risk has no influence to the capital structure. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â Keywords:Â  Assets Structure, Profitability, Investment Decision, Business Risk, Capital Structure